POLA KUMAN BERDASARKAN SPESIMEN DAN SENSITIVITAS TERHADAP ANTIMIKROBA - B Rusli; M Arief; Rostina Rostina; Hardjoeno Hardjoeno (Indonesian Association of Clinical Pathologist and Medical laboratory, 2006)
High prevalence of infectious diseases in Indonesia lead to the use of uncontrollable anti microbial treatment with less concern todrug resistance, marked with fewer requests for sensitivity testing. This leads to irrational anti microbial treatment and increasing drugresistance. With unsupported condition for using a sensitivity test prior to anti microbial treatment, a common guide for choosing ananti microbial agent for infection of specific organ system is needed. A descriptive study of retrospectively collected data of sensitivity testresults was done on 841 spesimens from sources of infected organs in Wahidin Sudirohusodo Hospital of Makassar during 2005–2006periods. Objectives of this study are to know the microbial pattern of specific organ infection (represented by microbes of the specimens),antimicrobial sensitivity pattern of the microorganisms, and whether there is shifting of the pattern within a 1 year period. Shiftingof microbial patterns during 2005–2006 period was found. Klebsiella aeroginosa, Enterobacter agglomerans, Alkaligenes faecalis andEscherichia coli were the most frequent micro organisms found from spesimens examined. Most of antimicrobial drugs commonlyused were found effective to most of micro organisms, while amikacin, cefepime, gentamycin, sulbactam, tobramycin, vancomycin andmeropene were still sensitive enough to the majority of the infectious agents.